2016
DOI: 10.1093/toxsci/kfw010
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-Oxide Nanoparticles Exhibit Genotoxic, Clastogenic, Cytotoxic and Actin Depolymerization Effects by Inducing Oxidative Stress Responses in Macrophages and Adult Mice

Abstract: Zinc oxide nanoparticles (ZnO-NPs) have wide biological applications, which have raised serious concerns about their impact on the health and environment. Although, various studies have shown ZnO-NP toxicity on different cells underin vitroconditions, sufficient information is lacking regarding toxicity and underlying mechanisms underin vivoconditions. In this work, we investigated genotoxic, clastogenic, and cytotoxic effects of ZnO-NPs on macrophages and in adult mice. ZnO-NP-treated mice showed signs of tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(67 citation statements)
references
References 74 publications
3
64
0
Order By: Relevance
“…Next, Vieira et al reported an alteration in cytoskeletal organization, including a change of cell polarity and the increase of F‐actin fiber formation, in HDF treated with AuNPs and AgNPs. Another result suggested that exposure of zinc oxide (ZnO) NPs to RAW 264.7 mouse macrophages resulted in F‐actin depolymerization and a decrease in the level of F‐actins . Fanarraga and co‐workers observed a reorganization of actin microfilaments into cell bundles and formation of aberrant F‐actin trails affecting proliferation and viability of human keratinocytes (HaCat) and cervical cancer cells (HeLa) after ZnO NPs treatment (Figure c).…”
Section: Effects Of Intracellular Nanoparticles On Adhesion Cytoskelmentioning
confidence: 94%
“…Next, Vieira et al reported an alteration in cytoskeletal organization, including a change of cell polarity and the increase of F‐actin fiber formation, in HDF treated with AuNPs and AgNPs. Another result suggested that exposure of zinc oxide (ZnO) NPs to RAW 264.7 mouse macrophages resulted in F‐actin depolymerization and a decrease in the level of F‐actins . Fanarraga and co‐workers observed a reorganization of actin microfilaments into cell bundles and formation of aberrant F‐actin trails affecting proliferation and viability of human keratinocytes (HaCat) and cervical cancer cells (HeLa) after ZnO NPs treatment (Figure c).…”
Section: Effects Of Intracellular Nanoparticles On Adhesion Cytoskelmentioning
confidence: 94%
“…Numerous in vitro and in vivo studies have demonstrated that ENMs have the potential to induce DNA damage (1921). For instance, zinc oxide nanoparticles (ZnO NPs) have been shown to exhibit genotoxic, clastogenic and cytotoxic effects (123). Zinc oxide nanoparticles are highly important due to their current and potential applications in biosensors, sunscreens, cosmetics, medicine and nutrition amongst others (124).…”
Section: Modifications Of the Automated Fadu Assaymentioning
confidence: 99%
“…Many researchers have demonstrated that gold NPs exhibit less cytotoxic and genotoxic effects compared to other nanomaterials like Zn and Ag NPs 36,37 . However, research in Drosophila melanogaster reported the gold NPs induces decreased infertility and numbers of progeny, increased in aberrant phenotype 38 .…”
Section: Discussionmentioning
confidence: 99%